In the End Was the Word: Speculative Fiction as a Stylistic Experiment. (1st October 2016) - Galina, Maria
Abstract : Maria Galina notes the greater stylistic freedom offered by genre fiction, including fantastika. She discusses Sergei Zharkovskii's 2005 novel I, Hobo: The Times of Death, and Elena Khaetskaia's 2010 novel The Fall of Sofia (comparing its mix of futurology with social and linguistic archaism to that in Vladimir Sorokin's 2010 Blizzard ) as worthy stylistic experiments. After mentioning Jasper Fforde's literature-focused novels, partly translated into Russian, Galina notes the hopelessness in the powers of language and literature expressed in Tatiana Tolstaya's Slynx and Vladimir Danikhnov's The Girl and the Dead .